2016
DOI: 10.1056/nejmc1612872
|View full text |Cite
|
Sign up to set email alerts
|

Cord-Blood Transplantation in Patients with Minimal Residual Disease

Abstract: BACKGROUND-The majority of patients in need of a hematopoietic-cell transplant do not have a matched related donor. Data are needed to inform the choice among various alternative donorcell sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Umbilical Cord Blood (CB), obtained at the time of delivery, is a good source of hematopoietic stem cells and a useful tool for stem cell transplantation for a variety of hematological and nonhematological malignancies and disorders (1,2). Compared to the conventional adult stem cell sources of bone marrow and peripheral blood, CB are associated with lower incidences of acute and chronic graft versus host disease (GVHD), while maintaining good graft versus leukemia (GVL) activity (3,4), possibly because of their tolerogenic cell composition, with a majority of naïve T cells and a high proportion of highly suppressive regulatory T cells (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical Cord Blood (CB), obtained at the time of delivery, is a good source of hematopoietic stem cells and a useful tool for stem cell transplantation for a variety of hematological and nonhematological malignancies and disorders (1,2). Compared to the conventional adult stem cell sources of bone marrow and peripheral blood, CB are associated with lower incidences of acute and chronic graft versus host disease (GVHD), while maintaining good graft versus leukemia (GVL) activity (3,4), possibly because of their tolerogenic cell composition, with a majority of naïve T cells and a high proportion of highly suppressive regulatory T cells (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cord blood transplants pose a minimal risk of clonal heterogenenity with the possibility of a final, dominant mutant clone. Retrospective studies looking at cord blood transplants have shown that they can perform well enough to minimize the difference in survival in patients with and without minimal residual disease at the time of transplantation [63]. This result is notable because it is a direct test of the clonal competitiveness of transplanted cord blood populations against a known leukemic population (minimal residual disease).…”
Section: Discussionmentioning
confidence: 99%
“…These findings led to the initiation of clinical trials using peripheral blood stem cell (PBSC) grafts depleted of naïve T cells, which showed lower rates of aGvHD and chronic GvHD (cGvHD) in HLA-matched HCT, with no apparent increase in relapse rates ( 14 ). On the other hand, cord blood grafts (in which almost all T cells are naïve) show great anti-leukaemic potential with reduced relapse risk but a similar likelihood of developing GvHD when compared to bone marrow grafts ( 15 ), indicating that T-cell intrinsic factors are contributing to the risk of GvHD development and anti-leukemic efficacy as well. Most significant associations between IR and clinical events were described for CD4 + rather than for CD8 + T cells, maybe because CD8 + T cell numbers fluctuate more swiftly in response to infections (e.g., CMV) or other events post-transplant ( 16 ).…”
Section: Distinct Importance Of Naïve and Memory T Cells And Significance Of T-cell Receptor Diversitymentioning
confidence: 99%